PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENGUNJUNG DI OBJEK WISATA RIAU FANTASI LABERSA WATER & THEMEPARK - Detmuliati, Alditia; Achnes, Syofia; Agus, Ari Kresnaputra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research has been performed to find the influence of the service quality to the guest satisfaction at Riau Fantasi Labersa Water & Themepark. On this research, the service quality was measured on Servqual tangibles (x.1), emphaty (x.2), reliability (x.3), responsiveness (x.4) and assurance (x.5). The research provided 140 respondents with accidental sampling as the sampling technique. The multiple linear regression was used as the analysis methods to obtain the test result of F, the test result of T and R2 was prepared by SPSS 16.00 program. The result of this research signify that simultaneously the service quality gave significant influence to the guest satisfaction. In partial, tangibles variable (x.1), reliability (x.3) and responsiveness (x.4) gave unsignificant influence to the service quality. Emphaty variable (x.2) and assurance (x.5) gave significant influence to the service quality.Keywords : Service Quality, Guest Satisfaction, SPSS